Primary small cell carcinoma of the esophagus: Comparison between a Chinese cohort and Surveillance, Epidemiology, and End Results (SEER) data - Qin Xiao; Haifan Xiao; Shuyu Ouyang; Jinming Tang; Baihua Zhang; Hui Wang (Cancer Medicine)
Abstract Background The optimal standard treatment for primary small cell carcinoma of the esophagus (SCCE) remains undetermined. In this study, we conducted two areas of research on SCCE. First, we analyzed differences in SCCE characteristics between Chinese and U.S. patients. Second, we evaluated optimal treatment strategies for SCCE in the Chinese cohort. Methods Data from 137 Chinese SCCE patients collected from two cancer centers in China were compared with 385 SCCE patients registered in the U.S. SEER program. Prognostic factors were further analyzed in the Chinese group. Propensity score matching (PSM) was used to balance baseline features between the groups. Results There were more Chinese SCCE patients with regional stage disease (41.6%) and surgery was the principal local therapy (78.1%), while 51.7% of U.S. patients was at advanced stages and tended to receive radiotherapy as the main therapy (45.2%). Median overall survival (MST) of Chinese patients was 15.0 months, compared with 8.0 months for U.S. patients (P < 0.001). However, the survival differences between groups disappeared after PSM (MST: 12.5 m vs 9.0 m, P = 0.144). Further analysis found that surgery tended to achieve clinical benefits only for patients with localized disease (T1‐4aN0M0). Radiotherapy and chemotherapy may prolong survival in patients with regional and extensive disease. Conclusions Although there are huge differences in the tumor characteristics and treatment modalities of SCCE between Chinese and U.S. patients, the prognosis of SCCE is equally poor in both. Surgery should be considered for patients with localized disease, while chemoradiotherapy is recommended for patients with regional and extensive disease.